1996
DOI: 10.1073/pnas.93.16.8384
|View full text |Cite
|
Sign up to set email alerts
|

Specific accumulation of tumor-derived adhesion factor in tumor blood vessels and in capillary tube-like structures of cultured vascular endothelial cells.

Abstract: Tumor-derived adhesion factor (TAF) was previously identified as a cell adhesion molecule secreted by human bladder carcinoma cell line EJ-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 35 publications
7
132
1
2
Order By: Relevance
“…Mac25/AGM is a secreted protein of ϳ30 kDa that is identical with previously reported molecules, including insulin-like growth factor binding protein related protein-1 (IGFBP-rP1) (7-9), tumorderived adhesion factor (10), which was later renamed AGM (11,12), and prostacyclin-stimulating factor (13). Mac25/AGM contains two major domains (9), which include an amino-terminal cysteine-rich domain containing the IGFBP motif that is conserved among IGFBPs and a C-terminal Ig-like domain.…”
Section: A High Endothelial Venule Secretory Protein Mac25/angiomodumentioning
confidence: 54%
See 1 more Smart Citation
“…Mac25/AGM is a secreted protein of ϳ30 kDa that is identical with previously reported molecules, including insulin-like growth factor binding protein related protein-1 (IGFBP-rP1) (7-9), tumorderived adhesion factor (10), which was later renamed AGM (11,12), and prostacyclin-stimulating factor (13). Mac25/AGM contains two major domains (9), which include an amino-terminal cysteine-rich domain containing the IGFBP motif that is conserved among IGFBPs and a C-terminal Ig-like domain.…”
Section: A High Endothelial Venule Secretory Protein Mac25/angiomodumentioning
confidence: 54%
“…Mac25/AGM contains two major domains (9), which include an amino-terminal cysteine-rich domain containing the IGFBP motif that is conserved among IGFBPs and a C-terminal Ig-like domain. Functionally, mac25/AGM has been implicated in various biological responses: it accumulates in the blood vessels of tumors (10), preferentially binds to extracellular matrix (ECM) components such as collagen type IV (10), promotes cell spreading of the human bladder carcinoma cell line ECV-304 on collagen type IV (10), and stimulates PGI 2 production, which is a potent vasodilator (13). It has been reported that mac25/AGM increases PGI 2 production in retinal endothelial cells, resulting in an increased retinal blood flow in vivo (14).…”
Section: A High Endothelial Venule Secretory Protein Mac25/angiomodumentioning
confidence: 99%
“…TGF-b mediates the transcription of several genes related to the ECM remodeling, including SPARC and collagen I (Reed et al, 1994), MMP-2, TIMP-1 (Kwak et al, 2006), plasminogen activator inhibitor-1 (Keeton et al, 1991) and collagen IV (Poncelet and Schnaper, 1998). Secreted IGFBP7 is known to interact with ECM components (Akaogi et al, 1996;St Croix et al, 2000), and could thus participate in the TGF-b1-induced ECM turnover and angiogenesis. Whereas inhibition of CLT formation was observed by TGF-b1 alone, in combination with VEGF and angiopoietin 1, CLT formation is rescued and stabilized, suggesting that the process is regulated by the interaction of angiogenic and antiangiogenic growth factors (Ramsauer and D'Amore, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the tumor suppressor role of IGFBP7 in cancer cells, IGFBP7 is highly upregulated in vessels of several tumors, including GBM (Akaogi et al, 1996;Pen et al, 2007), and interacts in vitro with various extracellular matrix (ECM) proteins to stimulate adhesion and migration/invasion of vascular endothelial cells on plastic substrates (Sato et al, 1999;Kishibe et al, 2000); hence, the original name 'angiomodulin' (Akaogi et al, 1996). Although literature evidence suggests that IGFBP7 might exhibit angiogenesis-modulating properties (Akaogi et al, 1996;van Beijnum et al, 2006), the role of IGFBP7 in tumor angiogenesis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation